Is Influencer Marketing Really a Lifesaver? - Kong, Hongqian (International Journal of Global Economics and Management, 2024)
In the digital age, influencer marketing has become one of the key strategies for branding. This essay explores the effectiveness of influencer marketing and its application in different market environments. Through a literature review and case studies, we find that influencer marketing has significant advantages in increasing brand awareness, driving sales and enhancing consumer loyalty. However, its effectiveness depends on a number of factors, including the credibility of the influencer, the engagement of fans, and the fit between the brand and the influencer. Despite the many potential benefits of influencer marketing, brands need to carefully select the right influencers and develop a clear strategy to maximize their ROI. This article summarizes current trends and future research directions in influencer marketing to help companies make better use of this marketing tool.